Teachers' Efforts to Improve Students' Learning Outcomes in Islamic Education through the Group Investigation Model at SD Negeri 084094 Sibolga - Azizi, Shofiah; Simanjuntak, Fitriyani; Siregar, Pida Satriani (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This study aims to improve student learning outcomes in Islamic Education using the Group Investigation Method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to improve student learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that learning with the Group Investigation Method can improve student learning outcomes. This can be seen from the increase in the percentage of completeness of improving student learning outcomes in each cycle with details of the pre-cycle 43.56%, the first cycle 78.57% and in the second cycle increased to 89.77%. Thus, the use of the Group Investigation Method can be used as an alternative to improve student learning outcomes.